p+4(-1)=3

Simple and best practice solution for p+4(-1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p+4(-1)=3 equation:



p+4(-1)=3
We move all terms to the left:
p+4(-1)-(3)=0
determiningTheFunctionDomain p-3+4(-1)=0
We add all the numbers together, and all the variables
p-7=0
We move all terms containing p to the left, all other terms to the right
p=7

See similar equations:

| 2/3y=41/4 | | 54.45=1x+76.45 | | −7x−5=23 | | 6x-3+9x-12+90=180 | | 4/5=0.5m | | -36-6x=-6(4+2x) | | Y-6=2(3x-4) | | a+6-2;a=-8 | | -4(x-5)-28=-10 | | y/9+4=-15 | | $13.75p+30=$57.50 | | 30h+50=40h+10 | | 3x2=12+5x | | 5x=-55 | | x^2-12x=x2−12x | | x(2x+4)-40=350 | | 23y=414 | | 2(r-10)=-16 | | 7(x-1)+2x+1=30 | | 3/10x+11=5 | | p+4(1)=3 | | 4x+7=-4x+4 | | j+6-2=2 | | -8y-4=16 | | x^2-12x=x2−12x= | | 6(x+5)=3x+11 | | -(k-2)-8(5+6k)=11 | | 4(n-7)+1=9 | | 0,1y+3y+0,9y=14+2y | | 5x+3x-12=20 | | 3=1x+99 | | 2x=x+1-3x |

Equations solver categories